Study of the Impact of Electronic Administration Policy Implementation and The Use of Artificial Intelligence on Bureaucratic Transformation in the Local Government Environment - Pasaribu, Johnson (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2022)
The purpose of this study was to determine and analyze the variables of electronic administration policy and the application of artificial intelligence to bureaucratic transformation in the Government environment through the variable of work effectiveness as a mediator variable...The subject of this study is the number of ASNs working in 37 Provinces in Indonesia, where the variables in this study are endogenous variables, namely the variables of electronic administration policy and the application of artificial intelligence, while the exogenous variable is bureaucratic transformation in the Government environment, and the mediator variable is the work effectiveness variable, where the data analysis used uses SEM analysis using SMART PLS 3.0 software.The research method used is to use a quantitative descriptive approach by using data analysis with the structural equation model (SEM) method, where the results of data processing with the SEM method are carried out with the PLS application. From the results of this study, the conclusion is that partially the variables of electronic administration policy and the use of artificial intelligence have an effect on bureaucratic transformation within the Provincial Government throughout Indonesia and also affect work effectiveness within the Provincial Government throughout Indonesia. Work effectiveness variables within the Provincial Government throughout Indonesia affect bureaucratic transformation within the Provincial Government throughout Indonesia. Simultaneously, the variables of electronic administration policy and the use of artificial intelligence affect bureaucratic transformation in the Provincial Government throughout Indonesia through work effectiveness in the Provincial Government throughout Indonesia. With the process of organizational digital technology transformation in MSMEs, it can increase the agility of the organization to be adaptive and able to change itself, as well as change the mindset of the owners of these MSMEs so that later they have a vision and mission that makes businesses on a medium and large scale, where MSMEs must be able to improve their quality and capacity so that MSMEs in Medan City can be known not only throughout the archipelago, but can also be known throughout foreign countries.